2009
DOI: 10.1021/ja807890a
|View full text |Cite
|
Sign up to set email alerts
|

Thiostrepton Biosynthesis: Prototype for a New Family of Bacteriocins

Abstract: Thiopeptide antibiotics are a group of highly modified peptide metabolites. The defining scaffold for the thiopeptides is a macrocycle containing a dehydropiperidine or pyridine ring, dehydrated amino acids, and multiple thiazole or oxazole rings. Some members of the thiopeptides, such as thiostrepton, also contain either a quinaldic acid or indolic acid substituent derived from tryptophan. Although the amino acid precursors of these metabolites are well-established, the biogenesis of these complex peptides ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
281
0
6

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(294 citation statements)
references
References 73 publications
7
281
0
6
Order By: Relevance
“…In this regard, the chemistry described by these systems is very different. In clostriodiolysin S, an amide carbonyl undergoes activation, as is the case for microcin B17, patellamide, goadsporin, and the recently described thiopeptide family (13)(14)(15)(16)27). Because ClosA contains a C-terminal asparagine, in addition to several Ser, Thr, B, shown is the genetic complementation of Clos genes in GAS M1 Sag mutants.…”
Section: Closa-d Genetic Complementation Studies In Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the chemistry described by these systems is very different. In clostriodiolysin S, an amide carbonyl undergoes activation, as is the case for microcin B17, patellamide, goadsporin, and the recently described thiopeptide family (13)(14)(15)(16)27). Because ClosA contains a C-terminal asparagine, in addition to several Ser, Thr, B, shown is the genetic complementation of Clos genes in GAS M1 Sag mutants.…”
Section: Closa-d Genetic Complementation Studies In Groupmentioning
confidence: 99%
“…ClosBCD resembles the McbBCD-modifying proteins found in the Escherichia coli microcin B17 system and the Prochloron didemni patDG genes of the patellamide biosynthetic gene cluster. This family of natural product toxins was recently shown by several groups to include the thiopeptides, which are nearly ubiquitous in soil-dwelling Bacillus and Streptomyces bacteria (12)(13)(14)(15)(16). In the microcin B17 system, McbB, -C, and -D were shown to be necessary and sufficient for the installation of heterocyclic moieties on C-terminal serine and cysteine residues of the McbA substrate.…”
mentioning
confidence: 99%
“…Recent genomeenabled studies have shown that many classes of peptide natural products initially suspected to be of nonribosomal origin are in fact gene-encoded (e.g., refs. [2][3][4][5][6] and that structural motifs previously thought to be found only in nonribosomal secondary metabolites are also found in ribosomally synthesized compounds (7). Clearly, synthesis of secondary metabolites via the ribosome turns out to be much more widespread than originally anticipated.…”
mentioning
confidence: 96%
“…The LanB dehydratases are 115-120 kDa proteins that do not share homology with the dehydratases from classes II-IV lanthipeptides or other proteins in the databases. Genes encoding homologous LanB-like enzymes are also present in the gene clusters of nonlantibiotic peptide natural products, such as the thiopeptides (16)(17)(18)(19) and goadsporin (20). These proteins are also believed to be dehydratases.…”
mentioning
confidence: 99%